DAMPAK PENDAMPINGAN DALAM MENGERJAKAN PR DAN KEBIASAAN ORANGTUA MEMBACA TERHADAP CAPAIAN AKADEMIK ANAK DALAM TIMSS 2015 - Liestari, Suci Paramitha; Safari, Safari (Pusat Asesmen dan Pembelajaran, 2019)
The success of student education cannot be separated from the schools, teachers, students and parents. Parents play an important role because they are the first and primary educators of their children. This study aims to assess the impact of parents’ support in helping their children to do their homework and parents' reading habits on mathematics and science scores in TIMSS 2015. By using quantitative descriptive and inferential methods, the analysis shows that parents who spend more time helping and checking their children homework, have children who achieve higher scores on mathematics and science. If they read more than 10 hours in 1 week, their kids scores on TIMSS 2015 significantly. Only 6,4% of parents whose reading habits more than 10 hours in 1 week.